Gut Microbiota-Derived Metabolites in Colorectal Cancer: The Bad and the Challenges - Zhang, Wanru; An, Yaping; Qin, Xiali; Wu, Xuemei; Wang, Xinyu; Hou, Huiqin; Song, Xueli; Liu, Tianyu; Wang, Bangmao; Huang, Xuan; Cao, Hailong (Frontiers in Oncology, 2021)
Accumulating evidence from studies in humans and animal models has elucidated that gut microbiota, acting as a complex ecosystem, contributes critically to colorectal cancer (CRC). The potential mechanisms often reported emphasize the vital role of carcinogenic activities of specific pathogens, but in fact, a series of metabolites produced from exogenous dietary substrates or endogenous host compounds occupy a decisive position similarly. Detrimental gut microbiota-derived metabolites such as trimethylamine-N-oxide, secondary bile acids, hydrogen sulfide and N-nitroso compounds could reconstruct the ecological composition and metabolic activity of intestinal microorganisms and formulate a microenvironment that opens susceptibility to carcinogenic stimuli. They are implicated in the occurrence, progression and metastasis of CRC through different mechanisms, including inducing inflammation and DNA damage, activating tumorigenic signaling pathways and regulating tumor immunity. In this review, we mainly summarized the intimate relationship between detrimental gut microbiota-derived metabolites and CRC, and updated the current knowledge about detrimental metabolites in CRC pathogenesis. Then, multiple interventions targeting these metabolites for CRC management were critically reviewed, including diet modulation, probiotics/prebiotics, fecal microbiota transplantation, as well as more precise measures such as engineered bacteria, phage therapy and chemopreventive drugs. A better understanding of the interplay between detrimental microbial metabolites and CRC would hold great promise against CRC.